Primary Ovarian Lymphoma: A Rare Entity - Pandit, Swoyam Prakash; Pandit, Sarbagya; Pandit, Shradha; Rauniyar, Amit (Nepalese Journal of Radiology, 2019)
Primary ovarian lymphoma (POL) refers to involvement of the ovary with lymphoma but without the involvement of any other site. It is an extremely rare yet well-recognized condition. We present to you a case of 25 year old female who presented with abdominal distension and mild lower abdominal pain for 4 weeks diagnosed radiologically and pathologically as primary ovarian lymphoma.